Incumbent upgrading in Nairobi's slums: How young people contribute to local spatial transformation - Andreas Eberth (Spatial transformation: Processes, strategies, research design, 2022)
This article summarises the results and findings of a study of young people in the slums of Nairobi based on participatory research methods. The study investigated the engagement of these young people, as a civil society that is growing in strength, and their contribution to a spatial transformation of the district in question.
urn:nbn:de:0156-08911016; hdl:10419/251347; https://econpapers.repec.org/RePEc:zbw:arlfob:19
Keywords: 710; Slum upgrading; governance; civil society; spatial transformation; Nairobi